COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE IN PROPERTY AND REAL ESTATE COMPANIES BEFORE AND DURING THE COVID-19 PANDEMIC - Thania Khairunnisa; Mira Munira; Shanti Lysandra (FEB-UP Press, 2022)
Abstract: The purpose of this study was to analyze the differences in the financial performance of property and real estate companies listed on the Indonesia Stock Exchange (IDX). This research method uses a quantitative descriptive method and the sampling is determined using purposive sampling with an observation period of 2 years, namely 2019-2020 and obtained 58 samples of companies with a data analysis process using descriptive statistics, normality tests and hypothesis testing. This study uses SPSS version 25 which shows that there are differences in the solvency ratio (DER), profitability ratios (ROA) and (ROE) before and during the Covid-19 pandemic and there are no differences in the liquidity ratio (CR), activity ratio (RTO) and solvency ratio (DAR) before and during the Covid-19 pandemic. Keywords: Covid-19 pandemic, Liquidity Ratios, Activity Ratios, Solvency Ratios and Profitability Ratios Abstrak: Tujuan dari penelitian ini adalah untuk menganalisis perbedaan kinerja keuangan perusahaan properti dan real estate yang terdaftar di Bursa Efek Indonesia (BEI). Metode penelitian ini menggunakan metode deskriptif kuantitatif dan pengambilan sampel ditentukan menggunakan purposive sampling dengan periode pengamatan 2 tahun yaitu 2019-2020 dan diperoleh 58 sampel perusahaan dengan proses analisis data menggunakan statistik deskriptif, uji normalitas dan pengujian hipotesis. Penelitian ini menggunakan SPSS versi 25 yang menunjukkan bahwa terdapat perbedaan rasio solvabilitas (DER), rasio profitabilitas (ROA) dan (ROE) sebelum dan selama pandemi Covid-19 serta tidak terdapat perbedaan rasio likuiditas (CR), rasio aktivitas (RTO). ) dan rasio solvabilitas (DAR) sebelum dan selama pandemi Covid-19. Keywords: Pandemi Covid-19, Rasio Likuiditas, Rasio Aktivitas, Rasio Solvabilitas dan Rasio Profitabilitas